RAG-Guardrails Integration for AI Content Control - Rakesh More (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Generative AI is particularly Large Language Models (LLMs), has shown remarkable potential across domains such as healthcare, legal services, and finance. However, their adoption is hindered by two persistent challenges: hallucination, where models generate factually incorrect information and the risk of producing biased or unsafe content. This paper proposes a hybrid framework that integrates Retrieval-Augmented Generation (RAG) with NVIDIA NeMo Guardrails to address these concerns. RAG mitigates hallucinations by grounding model outputs in externally retrieved, trusted data sources, while NeMo Guardrails enforce domain-specific safety and compliance constraints through predefined behavioral policies. Empirical evaluations demonstrate that this combined approach reduces hallucinated content by 30–45% and improves safety and policy adherence across multiple enterprise use cases. The system exhibits strong potential for deployment in regulated, high-stakes environments. Future work will focus on enhancing real-time responsiveness and expanding multilingual and culturally adaptive capabilities. The proposed framework offers a scalable foundation for building trustworthy, domain-aligned generative AI solutions.